The impact of the exposome on cytochrome P450-mediated drug metabolism - Ali, Hwaida; Hanna, Mireille M.; Alziny, Noha; Mahmoud, Shuaib; Borham, Abdallah; Mustafa, Aya; Abdelnaser, Anwar (Frontiers in Pharmacology, 2025)
The cytochrome P450 (CYP450) family of enzymes plays an important role in drug metabolism, toxicity, and individual responses to medications. Recent research has shown how the exposome, the sum of internal and external exposures during a person’s lifetime, significantly affects CYP450 function. The aim of this review is to investigate how different components of the exposome including external factors such as dietary substances, lifestyle choices, environmental pollutants, and internal factors such as gut microbiota, hormone fluctuations, and disease states, alter CYP450 expression and function, which in turn impacts drug metabolism and treatment outcomes. This review sheds light on the potential of personalized medicine and offers the promise for producing safer and more effective drug therapies in an increasingly dynamic exposure landscape by highlighting the molecular pathways that connect these exposures to alterations in drug metabolizing enzymes and their function.